2022
DOI: 10.1186/s12943-022-01569-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TGF-β signal transduction for fibrosis and cancer therapy

Abstract: Transforming growth factor β (TGF-β) has long been identified with its intensive involvement in early embryonic development and organogenesis, immune supervision, tissue repair, and adult homeostasis. The role of TGF-β in fibrosis and cancer is complex and sometimes even contradictory, exhibiting either inhibitory or promoting effects depending on the stage of the disease. Under pathological conditions, overexpressed TGF-β causes epithelial-mesenchymal transition (EMT), extracellular matrix (ECM) deposition, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
170
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(247 citation statements)
references
References 223 publications
4
170
1
Order By: Relevance
“…Coincidentally, Zeb1 and Zeb2 were also two members of zinc finger homobox family, and they shared similar molecular structures with ZFHX4 [ 45 ], which rendered the function of ZFHX4 as an EMT inducer reasonable. Besides, ZFHX4 could be modulated by canonical pathways for EMT regulation, such as TGF-β signaling pathway [ 46 , 47 ], which further supported the contributions of ZFHX4 to EMT. Simultaneously, we found the positive correlation between ZFHX4 and ECM-related genes.…”
Section: Discussionmentioning
confidence: 89%
“…Coincidentally, Zeb1 and Zeb2 were also two members of zinc finger homobox family, and they shared similar molecular structures with ZFHX4 [ 45 ], which rendered the function of ZFHX4 as an EMT inducer reasonable. Besides, ZFHX4 could be modulated by canonical pathways for EMT regulation, such as TGF-β signaling pathway [ 46 , 47 ], which further supported the contributions of ZFHX4 to EMT. Simultaneously, we found the positive correlation between ZFHX4 and ECM-related genes.…”
Section: Discussionmentioning
confidence: 89%
“…Transforming growth factor-β (TGF-β) is the key regulator of cancer metastasis and fibrosis diseases. 15 As our group′s ongoing research on natural TGF-β inhibitors, 16 18 compounds 1 and 2 were tested for in vitro TGF-β inhibitory activity. The results showed that only compound 1 significantly downregulated the TGF-β-induced p-Smad2 expression in a concentration-dependent manner without any impact on the expression of Smad2/3 protein in MDA-MB-231 cells ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Transforming growth factor-β (TGF-β) is the key regulator of cancer metastasis and fibrosis diseases . As our group′s ongoing research on natural TGF-β inhibitors, compounds 1 and 2 were tested for in vitro TGF-β inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the two signaling pathways are also intertwined with one another in noncanonical fashion, i.e. TGFβ is also known to be capable of activating signal proteins in the RAS/MAPK or PI3K/AKT pathways 11 . Other CAF-DE-miRNAs, such as miR-136-5p, miR-137-3p, miR-139-5p and miR-139-5p are also actively involved (suppl.…”
Section: Resultsmentioning
confidence: 99%